(untitled) (Economics and region, 2025)
This paper presents a comprehensive macroeconomic and econometric analysis of the structural transformation and growth dynamics of Azerbaijan’s non-oil sector amid heightened global market volatility and the strategic push for economic diversification. Drawing on quarterly data from 2017 to 2025, the study explores changes in GDP composition, sectoral investment trends, and their macro-level interactions. The regression results confirm a robust positive effect of non-oil GDP growth on total GDP, while foreign investments exhibit a moderate yet negative short-term impact. The findings highlight the increasing significance of the non-oil sector as a key driver of sustainable, inclusive, and shock-resilient economic development in Azerbaijan. The paper emphasizes the importance of investment structure and institutional quality in shaping long-term economic outcomes. Policy implications suggest that strengthening domestic value chains and reducing import dependence are crucial for enhancing the sector’s contribution to national growth.